2009
DOI: 10.1097/mph.0b013e3181978fd4
|View full text |Cite
|
Sign up to set email alerts
|

Fitness of Children With Standard-risk Acute Lymphoblastic Leukemia During Maintenance Therapy

Abstract: These results suggest that a home-based exercise intervention during maintenance therapy encouraged greater physical activity and improved cardiovascular fitness in children with standard-risk ALL. Further investigation involving larger populations of children with ALL is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
207
1
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(221 citation statements)
references
References 27 publications
(35 reference statements)
5
207
1
8
Order By: Relevance
“…Our findings suggest that the first year of maintenance therapy should be targeted for preventive exercise and nutrition interventions, which will support the return to a healthy lifestyle. Several pilot studies have demonstrated feasibility of such an approach (23)(24)(25), but larger scale trials of efficacy are warranted. Schema for Children's Oncology Group Protocols (treated on or according to AALL0331 or AALL0232) with notation as to when corticosteroids and cranial radiation is given.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that the first year of maintenance therapy should be targeted for preventive exercise and nutrition interventions, which will support the return to a healthy lifestyle. Several pilot studies have demonstrated feasibility of such an approach (23)(24)(25), but larger scale trials of efficacy are warranted. Schema for Children's Oncology Group Protocols (treated on or according to AALL0331 or AALL0232) with notation as to when corticosteroids and cranial radiation is given.…”
Section: Discussionmentioning
confidence: 99%
“…A 20-week aerobic intervention of thrice weekly activity for 30-40 min after treatment improved fitness in Hodgkin lymphoma survivors. 70 In a 12-month home-based aerobic and resistance training RCT, Moyer-Mileur et al 44 found a significant increase in self-reported physical activity and fitness, but no increase in objectively measured physical activity (pedometer-measured steps). A small intervention study that included supervised and home-based exercise increased physical activity.…”
Section: Adultsmentioning
confidence: 99%
“…Twelve studies, [42][43][44][45][46][47][48][68][69][70][71][72] including two RCT 42,44 and seven high-quality studies [42][43][44][45][46]69,71 evaluated the effects of physical activity interventions on outcomes in children with pediatric cancer who did not undergo HSCT. One study of high quality 68 evaluated the effects of a single (30 min) exercise bout.…”
Section: Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Review more patients (21,25,(27)(28)(29)(30)(31)(32)(33)(34). Five randomized, controlled trials have been identified (28)(29)(30)(31)33) and were ranked with evidence level "2b. "…”
Section: Exercise In Pediatric Oncologymentioning
confidence: 99%